1999
DOI: 10.1017/s0043174500092067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and photoperiod onSetaria viridis

Abstract: Understanding the environmental variables influencing the phenological development of weeds is essential for simulation model development. Temperature and photoperiod are important variables governing the phenological development of weeds. Growth cabinet studies were conducted to characterize the phenological development ofSetaria viridisin response to variations in temperature and photoperiod and to determine the duration of the juvenile phase and the effect of temperature and photoperiod on reproductive deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
16
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 21 publications
10
16
1
Order By: Relevance
“…This finding is in contrast to green foxtail, where sensitivity to photoperiod was apparent only up to initiation of heading and further phenological development was independent of photoperiod. The number of thermal days required to reach initiation of flowering, seed set, and end of seed set was similar across all photoperiods (Swanton et al, 1999) Our results for barnyardgrass, however, agree with the findings of Vengris et al (1966) They reported that plants under a LD (16 h) condition headed and produced mature seeds much later than similar plants under SD (11 h) conditions. In an 11‐h photoperiod, barnyardgrass headed about 35 DAE and produced mature seeds at about 52 DAE, whereas under a 16‐h photoperiod, heading occurred at about 53 DAE and produced mature seeds at 90 DAE.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…This finding is in contrast to green foxtail, where sensitivity to photoperiod was apparent only up to initiation of heading and further phenological development was independent of photoperiod. The number of thermal days required to reach initiation of flowering, seed set, and end of seed set was similar across all photoperiods (Swanton et al, 1999) Our results for barnyardgrass, however, agree with the findings of Vengris et al (1966) They reported that plants under a LD (16 h) condition headed and produced mature seeds much later than similar plants under SD (11 h) conditions. In an 11‐h photoperiod, barnyardgrass headed about 35 DAE and produced mature seeds at about 52 DAE, whereas under a 16‐h photoperiod, heading occurred at about 53 DAE and produced mature seeds at 90 DAE.…”
Section: Resultssupporting
confidence: 89%
“…For example, Muldoon et al (1982) reported that the relative growth rate and accumulation of shoot dry weight of Japanese barnyard millet ( Echinochloa utilis Ohwi et Yabuno) and paisa ( E. frumentacea L.) were positively correlated with an increase in temperature from 15/10 to 33/28°C. Rate of leaf appearance in velvetleaf ( Abutilon theophrasti L.) also increased with temperature from 12/4 to 26/18°C and declined at higher temperatures (Patterson, 1992) Similarly, Swanton et al (1999) reported that the rate of leaf and tiller appearance and shoot elongation of green foxtail increased with temperature up to 35/25°C and declined at higher temperatures.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations